Decline in Cryptosporidium Infection in Free-Ranging Rhesus Monkeys in a Park After Public Health Interventions - Jia, Ruilian; Wen, Xi; Guo, Yaqiong; Xiao, Lihua; Feng, Yaoyu; Li, Na (Frontiers in Cellular and Infection Microbiology, 2022)
Nonhuman primates (NHPs) are considered an important source of parasitic zoonoses. A study in 2010 revealed high prevalence of Cryptosporidium spp. in free-ranging rhesus monkeys (Macaca mulatta) in a public park in Guiyang, southwestern China, which called for the control of disease in animals and long-term epidemiological tracking of Cryptosporidium spp. After the initiation of a series of public health interventions, we collected 2,402 fecal samples from monkeys and 123 water samples from lakes in the park on six occasions during 2013-2019. They were analyzed and genotyped for Cryptosporidium spp. using PCR and sequence analyses of the small subunit rRNA gene. The C. hominis and C. parvum identified were further subtyped by sequence analysis of the 60 kDa glycoprotein gene. Compared with the high prevalence of Cryptosporidium spp. in fecal samples (10.9% or 45/411) and water samples (47.8% or 11/23) in 2010, only 18 (0.7%) fecal samples and 3 (2.4%) water samples collected in the present study were positive for Cryptosporidium spp., including C. hominis (n = 9) and C. parvum (n = 12). The former belonged to the NHP-adapted IfA17G2R3 subtype, while the latter mostly belonged to rodent-adapted IIpA9. Therefore, the detection rate and genetic diversity of Cryptosporidium spp. during this study period were much lower than those before the public health interventions, and there was a switch from common occurrence of anthroponotic C. hominis subtypes to sporadic occurrence of NHP-adapted C. hominis and rodent-adapted C. parvum subtypes.